Universidade Aberta's pedagogical model for distance education: a university for the future - Pereira, Alda (2013)
This document present the Pedagogical Model for Distance Education in the case of Universidade Aberta of Portugal. It describes the principles and actions for the fully virtualization of the organization and for the learning process.